Effect of ferulic acid sugar ester with high molecular mass from corn bran on proliferation of intestinal bifidobacteria in aged mice induced by D‐galactose: The role of HFASE in the intestine. Issue 11 (7th August 2019) - Dai, Junling; Zhang, Wei; Geng, Xin
Abstract: Our experiment was to study the effect of high molecular mass ferulic acid sugar ester (HFASE) from corn bran on proliferation of intestinal bifidobacteria in aged mice induced by D‐galactose. The number of bifidobacteria in the intestine of D‐galactose‐induced aging mice was lower than that of normal mice. After the intragastric administration of different doses of HFASE (100, 200, and 300 mg kg −1 day −1 body weight) in experimental groups, the number of bifidobacteria was also higher than the aging group. The proliferation rate of bifidobacteria in the intestine of the experimental groups was fast in the first 24 days of feeding and then tended to be gentle. The H‐l experimental group (100 mg/kg body weight) had the most obvious effect of the proliferation of bifidobacteria. Practical applications: As the by‐product of corn starch processing, corn bran was usually processed into animal feed and sold at a low price. The results of this study indicated that high molecular mass corn bran ferulic acid sugar ester had the effect of promoting the proliferation of bifidobacteria in aging mice, which provided ideas for the development and application of corn bran in the food industries. It could be added as a raw material for functional foods to common foods such as yogurt, baked bread, cereals, and porridge.